Tsunami Overtopping Fan and Erosive Scarps at Atlantic Coast of Tierra Del Fuego - Bujalesky, Gustavo Gabriel (2012)
The Ensenada de la Colonia embayment, North-Eastern Tierra del Fuego, presents an extensive and wide Holocene beach ridge plain composed of gravel and coarse sand. These deposits have revealed a regressive behavior since 6000 yr B.P. A Pleistocene gravel beach ridge plain was recognized in the area. Several erosive scarps are present at the embayment, indicating strong and episodic erosive events. Seaward and immediately behind the present storm berm, a high and unique overtopping fan develops. Tierra del Fuego is a seismic area and the subduction zone of the South Sandwich Islands constitutes a potential source of tsunamis. The abrasion platform of embayment shows a glacifluvial carved paleomorphology. This feature conditions the wave refraction pattern, concentrating the orthogonal rays in its central section. In this setting, a tsunami backwash could generate mega-vortexes in the nearshore zone of the bay linked to the depressed areas of the abrasion platform. The combined action of a large seepage, tsunami backwash currents and tangential currents of the vortex applied on saturated gravel beaches would cause carving of the lower section of the beach and instability of the entire profile. Then collapses of relevant volumes of gravel and sand would lead to the formation of semi-circular erosive scarps. The overtopping fan architecture displays a sequence of 3 to 5 landward overlapping radar facies of overwashing and overtopping events. The semicircular erosive scarps and the overtopping fan were originated by tsunamis that reached the Atlantic coast of Tierra del Fuego. At least three pulses of a unique tsunami episode constructed the overtopping fan.